Panglukatan Sapta Gangga Sebagai Media Penyuluhan Agama Hindu Di Pura Luhur Tambawaras Desa Sangketan Kecamatan Penebel Kabupaten Tabanan - Ni Wayan Indrayani (Jayapangus Press, 2019)
The existence of the Panglukatan Sapta Gangga is currently the talk and the main objective for the activities and spiritual journey that targets the Panglukatan location. The condition of the Panglukatan is relatively new but has various functions and religious and spiritual meanings, and considering that there are so many Hindus who do not understand the meanings contained in the commemoration program it requires more optimal arrangement. Therefore it is necessary to disseminate the teachings of religion to the people, so that the people believe and understand the meanings contained in a religion so that it can be practiced in living their daily lives. The problems discussed are the first regarding the existence of Panglukatan Sapta Gangga in Luhur Tambawaras Temple, Sangketan Village, Penebel District, Tabanan Regency dissected using religious theory, the results of the research include history, structure, Panglukatan Sapta Gangga, upakara and malukat provisions. Secondly, the function of Panglukatan Sapta Gangga in Luhur Tambawaras Temple, Sangketan Village, Penebel District, Tabanan Regency was dissected using structural functional theory, the results of the study showed that Panglukatan Sapta Gangga as a Cleaning / Cleansing Media, Panglukatan Sapta Gangga as Medicinal Media / Usadha, Panglukatan Sapta Gangga As Media Religious Counseling. Third, concerning the impact of the existence of Sapta Gangga Commando in Luhur Tambawaras Temple, Sangketan Village, Penebel District, Tabanan Regency was dissected using behavioral theory, with the results of the discussion including cognitive impact (changes in knowledge), affective effects such as emotional and feelings changes, and behavioral impacts related to behavior. the community